Concentration and the Second Stage of Labor: Outcomes Associated with the Interactive Metronome - McGowan, Meghan L.; Lin, Alexander; Ou-Yang, Robin; Zei, Markus; Grobman, William (American Journal of Perinatology, 2012)
Objective To analyze the association between concentration, as measured by the Interactive Metronome, and a prolonged second stage of labor in nulliparous patients.Study Design From September 2008 to November 2009, nulliparous women at ≥34 weeks' gestation who were planning to use an epidural were asked to perform a 1-minute Interactive Metronome clapping test. Scores and demographic information were recorded. Data were then abstracted regarding each patient's labor course. The main outcome measure was the frequency of the second stage of labor exceeding 2 hours. Only patients with epidural anesthesia who completed the second stage of labor and did not require operative delivery performed for fetal indications prior to 2 full hours of pushing were included.Results Of the patients whose Interactive Metronome test scores were in the last quartile, which we associated with poor concentration, 52.9% (18/34) had a second stage of labor exceeding 2 hours compared with only 31.7% (33/104) of patients whose scores placed them in the first three quartiles (p = 0.026).Conclusion Nulliparous patients with poor concentration scores, as measured by the Interactive Metronome, were more likely to push greater than 2 hours in the second stage of labor.
Keywords: concentration; labor; pushing; interactive metronome